An Innovative Way to Turn Catalyst into Substrate for Highly Efficient Water Splitting. Issue 35 (2nd July 2021) - Kim, Hye Ri; Lee, Gahyeon; Nam, Gyeong Duk; Kim, Dongyoung; Joo, Jong Hoon
Abstract: The energy‐efficiency loss with high overpotential during hydrogen evolution reaction (HER) and oxygen evolution reaction (OER), as well as economic inefficiencies including high‐cost materials and complicated processes, is considered the major challenge to the implementation of electrochemical water splitting applications. The authors present a new platform for electrocatalysts that functions in an unprecedented way to turn a catalyst into substrate. The NiFe alloy catalyzed substrate (NiFe‐CS) described herein is substantially active and stable electrocatalyst for both HER and OER, with low overpotential of 33 and 191 mV at 10 mA cm −2 for HER and OER, respectively. This structure enables not only the maximization of electrochemically active sites, but also the formation of hydroxyl species on the surface as the active phase. These outstanding results provide a new pathway for the development of electrocatalysts used in energy conversion technology. Abstract : A NiFe alloy catalyzed substrate is designed via a novel conversion process that turns catalysts into the substrate for bifunctional water splitting electrodes. Benefiting from the multi‐scale pore structure of catalyzed substrate with large surface area, efficient gas diffusion, and superior charge transfer, the NiFe alloy catalyzed substrate exhibits outstanding activity and durability for HER and OER simultaneously.